Electrical Behavior of a Nanoporous Nb2O5/Pt Schottky Contact at Elevated Temperatures - Khairir, Nur Samihah; Abdul Rani, Rozina; Ab Kadir, Rosmalini; Soin, Norhayati; Abdullah, Wan Fazlida Hanim; Mamat, Mohamad Hafiz; Rusop, Mohamad; Zoolfakar, Ahmad Sabirin (Springer, 2019)
This paper discusses the effects of temperature on Schottky behavior of anodized niobium pentoxide (Nb2O5) used to form a nanoporous structure film. The application of a typical Schottky diode is limited at high temperature, and studies of different materials used in the fabrication are still in demand. Nb2O5 as a Schottky diode operation at elevated temperature has yet to be investigated. A nanoporous structure has the potential of producing high conductivity and also has the ability to spread heat since it has higher surface area. The structure was synthesized by anodizing niobium foils in ethylene glycol-based solution with 0.4 wt.% of H2O in different anodization times; 4 min, 8 min, 10 min, 40 min and 60 min. The anodized films were then annealed for 30 min at 440°C. The metal contact used for current–voltage (I–V) testing was platinum (Pt) and it was deposited via thermal evaporator at 30-nm thickness. Various characterization tests were conducted. Field emission scanning electron microscopy (FESEM) images suggested that longer anodization time produced larger pore sizes. The x-ray diffraction (XRD) confirmed the crystallization of Nb2O5 to be in an orthorhombic phase, while atomic force microscopy (AFM) showed surface roughness decreasing with longer anodization time. Higher surface roughness produced lower leakage current. I–V tests were conducted under different temperatures of 25°C, 50°C, 75°C, 100°C and 125°C to study the heat effect on I–V Schottky behavior of anodized nanoporous Nb2O5. By testing the I–V characteristics at elevated temperature, the electrical parameters were observed to have strong dependency on temperature. A device with lower thickness and operating at higher temperature produced higher current contribution. From I–V tests, it was observed that the increment of barrier height and decrement of ideality factor will be affected by increased temperature. For Schottky Pt/Nb2O5, barrier height increased in the range from 0.91 to 1.05, while the ideality factor decreased from 2.24 to 1.42.